Santa Cruz de la Sierra, a city that searchs for its own space (Ciudades, 2018)
This text analyzes the urban structure of Santa Cruz de la Sierra, Bolivia, from its colonial origins, with a grid plan, to the growth produced in S. XX. It explains the causes an the urban plannings, based on a radio- concentric model, that the city has followed.
Keywords: grid; radio-concentric model; ring; neighbourhood unit; informal sector